ANISOTROPIC PROPERTIES OF THE UPPER MANTLE IN CENTRAL ASIA ACCORDING TO THE GROUP VELOCITY DISPERSION CURVES FOR RAYLEIGH AND LOVE WAVES - A. I. Seredkina; O. A. Solovey (Геодинамика и тектонофизика)
The article presents the results of the study focused on the anisotropic properties of the upper mantle in Central Asia. The study is based on a representative set of the group velocity dispersion curves for Rayleigh and Love waves. The dispersion curves were calculated in the range of 10–250 s. The maps of group velocity distribution pat‐ terns and the horizontal resolution estimates were calculated by the surface‐wave tomography method developed for a spherical surface. Based on the maps, the local group velocity dispersion curves were reconstructed for the given points within the study region, which were then converted into the one‐dimensional velocity sections of SV‐ and SH‐waves, and a vertical anisotropy coefficient was estimated. A three‐dimensional anisotropic model shows the ve‐ locity distribution pattern of S‐waves in the crust and the mantle to the depth of 500 km. According to this model, ver‐ tical anisotropy in the upper mantle is observed to the depth of about 250 km and has maximum values in the depth interval from the crustal bottom to 150 km. The anisotropic properties are unevenly distributed and reflect the geo‐ logical structure of the study area. Therefore, tectonically active regions are characterized by the high values of the anisotropy coefficient and the reduced values of the S‐wave velocities. The presented results can contribute to the further development of more detailed and strictly proved geodynamic models of the study area.